SISTEM PENDUKUNG KEPUTUSAN PROGRAM KOTAKU DI WILAYAH SEBERANG KECAMATAN PELAYANGAN KOTA JAMBI - Mulyati, Sri; ., Jetendra (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2019)
The No Slum City Program (Kotaku) is one of a number of strategic efforts of the Directorate General of Human Settlements of the Ministry of Public Works and Public Housing to accelerate the handling of slums in Indonesia and support the Movement 100-0-100, namely 100 percent universal access to drinking water, 0 percent of settlements slum, and 100 percent access to proper sanitation. The direction of the Directorate General of Cipta Karya's development policy is to build a system, facilitate local government, and facilitate the community (community based). The Kotaku program will handle slums by building a collaboration platform through increasing the role of local government and community participation. But the handling of the Kotaku program is experiencing problems because each community feels its area is the most priority for my city program. With the Decision Support System using Simple Addictive Weighting (SAW) method where this method of assessment is done by looking for weight values for each criterion, then a ranking process is carried out that will determine the best alternative priority projects to be worked on. That way the problems that occur in my city program can be resolved properly.